RESEARCH ON BEAMFORMING TECHNIQUES IN 5G NETWORK - Hoang Van Thuc*, Doan Manh Cuong (Tạp chí Khoa học)
5G networks mark a significant advancement in telecommunications standards compared to 4G, offering data transmission speeds of up to 10 Gbps and are expected to be widely deployed shortly. Achieving this speed requires high- frequency waves over a broad bandwidth, presenting various technical challenges. One of the key technologies supporting 5G is Massive MIMO Beamforming, particularly Hybrid Beamforming - a combination of Analog and Digital Beamforming - that optimizes signal transmission without distortion. In this study, the author has simulated, compared, and evaluated the performance of three Beamforming techniques: conventional, adaptive, and hybrid. The analysis results help identify the most optimal method for enhancing communication efficiency in 5G networks, contributing to this technology's practical application and deployment.